THE EFFECT OF ORGANIZATIONAL FAIRNESS AND JOB CHARACTERISTICS ON EMPLOYEE ATTACHMENT - Riski Ulan Sari; Rd Roro Anggraini Soemadi; Hendra Galuh Febrianto; Humairoh (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to determine the Effect of Organizational Justice and Job Characteristics on Employee Attachment to PT. Ching Luh Indonesia, either partially or simultaneously at PT. Ching Luh Indonesia. This study used associative method with quantitative approach. A lot of sampling was 78 people. Descriptive data analysis techniques are used to determine the picture of respondents' answer responses and data distribution, while inferential statistical analysis is for hypothesis testing. Data processing is assisted by Microsoft excel and SPSS software version 25. Based on the correlation test of Organizational Fairness (X1), and Job Characteristics (X2) with Employee Attachment (Y) have a strong relationship. Organizational Fairness and Job Characteristics can project Organizational Fairness with a positive influence, this can be seen from the equation Y = 2.881 + 0.622X11 + 0.304X21 which means that the higher or increased the Employee Attachment. Organizational Fairness and Job Characteristics contributed 55.30% while the remaining 44.70% was influenced by other variables classified in epsilon, namely other factors that affect Employee Attachment but were not careful in this study.